Gas emission funnels as an object of geocryology (Part 1) - Khimenkov, Aleksandr Nikolaevich; Stanilovskaya, Julia Viktorovna (Арктика и Антарктика, 2025)
This publication is the first part of an article that demonstrates the significant role of the cryogenic factor in the preparation of pneumatic explosions within the body of permafrost rocks, based on an analysis of data available in scientific literature. The object of the study is local cryogenic gas-dynamic geosystems, the development of which leads to pneumatic explosions and the formation of gas blowout craters. The subject of the study is the morphology and structure of cryogenic formations in frozen rocks that make up the gas blowout craters found in the northern part of Western Siberia. The authors thoroughly examine aspects of the topic such as the analysis and generalization of data on the cryogenic structure of various elements in gas blowout craters. Special attention is given to the study of various deformations of primary ice formations, which allows tracking the history of the emergence and development of local gas-dynamic geosystems within permafrost rocks. The authors do not address questions related to the genesis of gas, as they believe that the pressure processes occurring in local gas-saturated zones with increased pressure do not depend on its origin. The main method used in this article is the analysis of materials from scientific publications on the subject, as well as laboratory modeling data conducted by the authors. The synthesis of the analyzed materials is based on a geosystemic approach. A significant contribution of the authors to the study of the topic is the identification of a common pattern in the structure of gas blowout craters. All craters that are not filled with water and are accessible for study exhibit a three-part structure. At the bottom of the craters, an expansion is observed, sometimes due to caverns and grottoes. In the middle part, the cross-section of the craters decreases, and the walls of the crater are most often steep and even. In the upper part, an expansion is observed in the shape of a flare. The novelty of the research lies in uncovering the paragenetic relationships between the morphological structure of the craters, the stages of development of the gas-dynamic geosystem that prepares conditions for pneumatic explosions, and the complexes of processes at each stage. The main conclusions of the research include the identification of the leading role of gas pressure in the transformation of the cryogenic structure of frozen rocks at all stages.